A facile method for Rh-catalyzed decarbonylative ortho-C–H alkylation of (hetero)arenes with alkyl carboxylic acids. Issue 32 (2nd June 2021) - Tian, Yiqiang; Liu, Xiaojie; He, Bangyue; Ren, Yuxi; Su, Weiping
Abstract : A facile and effective method for Rh-catalyzed direct ortho -alkylation of C–H bonds in (hetero)arenes with commercially available carboxylic acids has been developed. Abstract : A facile and effective method for Rh-catalyzed direct ortho -alkylation of C–H bonds in (hetero)arenes with commercially available carboxylic acids has been developed. This strategy was initiated by in situ conversion of carboxylic acids to anhydrides which, without isolation, underwent Rh-catalyzed direct decarbonylative cross-coupling of aryl carboxamides containing 8-aminoquinoline. The reaction proceeds with high regioselectivity and exhibits a broad substrate scope as well as functional group tolerance.